AKOMODASI ‘URF TERHADAP UPAYA PRIBUMISASI FIKIH MU’ÂMALÂT DI INDONESIA - Akmal Bashori (DIKTUM: Jurnal Syariah dan Hukum, 2019)
Urf (tradition) is an aspect that can not be separated from humans, because ‘urf is an integral whole with actions that are repeatedly practiced and agreed upon by the local community. This tradition becomes a cultural symbol in which the culture (‘urf) in the perspective of fiqh epicemology becomes one of the elements in its formulation. The effort of indigenous jurisprudence mu’âmalât through cultural channels reap a positive response in society that is still recognized its existence. Like the principle of mutual “legowo” (QS 4: 29), the tradition of "maro" in the fiqh of mu’âmalât is called mudharobah, tradis “Ijon” (salam). All of it gets the legitimacy of Jurisprudence because fiqh is responsive and accommodative to the ‘urf, in addition to the basic law of fiqh mu’âmalât is permissible.